2019
DOI: 10.1117/1.jbo.25.1.014507
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of intraerythrocytic hemozoin by transient absorption microscopy

Abstract: Hemozoin, the heme detoxification end product in malaria parasites during their growth in the red blood cells (RBCs), serves as an important marker for diagnosis and treatment target of malaria disease. However, the current method for hemozoin-targeted drug screening mainly relies on in-vitro β-hematin inhibition assays, which may lead to false-positive events due to under-representation of the real hemozoin crystal. Quantitative in-situ imaging of hemozoin is highly desired for high-throughput screening of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Because Hzn is such a prominent feature of intraerythrocytic stages, it has become a simple metric for identifying parasite stage and maturation. Recently, it has been shown that transient absorption can distinguish between Hb and Hzn based on subtle differences in transient absorption lifetime . We confirmed that the same differences between Hb and Hzn are present for the much longer wavelength pair used in our study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Because Hzn is such a prominent feature of intraerythrocytic stages, it has become a simple metric for identifying parasite stage and maturation. Recently, it has been shown that transient absorption can distinguish between Hb and Hzn based on subtle differences in transient absorption lifetime . We confirmed that the same differences between Hb and Hzn are present for the much longer wavelength pair used in our study.…”
Section: Resultssupporting
confidence: 90%
“…Recently, it has been shown that transient absorption can distinguish between Hb and Hzn based on subtle differences in transient absorption lifetime. 44 We confirmed that the same differences between Hb and Hzn are present for the much longer wavelength pair used in our study. Figure 5B reports the SRS spectrum of blood plasma (white box) and the transient absorption lifetime of a healthy RBC (red box) and an infected RBC (blue box).…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…In a detoxification mechanism the oxidised iron group is compacted into an insoluble crystalline form: β-hematin or haemozoin and stored in the food vacuole (36), becoming a distinct feature of intra-erythrocytic Plasmodium parasites (32). Intracellular haemozoin formation is reliably detected 12 to 18 hours postinfection and both crystal size and number increase with progression of the blood cycle (37,38). The flow cytometry strategy to detect depolarisation of light caused by hemozoin therefore ensures that the events detected correspond to parasites that have successfully invaded differentiated cells, survived and started growing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more than one imaging modality has been integrated into the IVUS images. For example, IVUS/intravascular optical coherence tomography (IV-OCT) [184][185][186][187][188][189] and IVUS/near-infrared spectroscopy (NIRS) [190][191][192][193][194] are currently available for practical use, and IVUS images with near-infrared fluorescence (NIRF) [195][196][197][198][199], fluorescence lifetime imaging (FLIm) [200][201][202][203][204], and intravascular photoacoustic (IVPA) [123,[205][206][207][208] have been investigated at the laboratory level. These combinations can complement the drawbacks of each imaging modality while providing more clinical information.…”
Section: Discussionmentioning
confidence: 99%